The African Union policies towards the Western Sahara - Omar, Sidi (Africana Studia, 2020)
The article will examine the policies pursued by the African Union (AU), as an intergovernmental organisation, with regard to the question of Western Sahara, commonly referred to as Africa’s last colony. It will outline some defining moments that have shaped the policies of the African continental organisation and informed its engagement with the question of Western Sahara over the past decades. Overall, the article will demonstrate that, although it has been actively involved in the question of Western Sahara, the AU still faces certain structural and political constraints that have so far prevented it from having a major role as an active player in the management and resolution of the longest running conflict on the continent. Keywords: African Union, Decolonisation, Organisation of African Unity, Western Sahara.